(untitled) (Journal of Management and Educational Sciences, 2024)
The aim of this research is to examine the effect of inequality in income distribution as a result of neoliberal policies. For this purpose, the document analysis method, which is one of the qualitative studies, was used. According to the results of the research, the global crises that emerged in the markets of developed countries revealed the shortcomings of an economic policy approach that believes in the self-regulation of the markets and minimizes the role of the state. As a result of neoliberal policies, the increasing importance of finance for corporate profitability has led to widening income inequality. Taken together, there is clear evidence that liberalization indirectly widens inequality by increasing financial activities. Therefore, this study reveals the role of the state as a social state again, based on the potential liberalization-finance-income inequality link in economies.